TARAS SHEVCHENKO’S HISTORIC-SOPHIC CONCEPTS - Kozak, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights the problem of historic-sophic concepts of Taras Shevchenko’s creations. It is proved on the rich artistic material, particularly on the writer’s poems, that historic sophism is an inseparable constituent of the poet’s ideological-aesthetic conscience.